EVALUASI IMPLEMENTASI KEBIJAKAN PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KABUPATEN KUDUS - Putri Lestari; Ahmad Taufiq; Purwoko . (Journal of Politic and Government Studies, 2016)
According to UU No. 32 of 2004 on Regional Government is expected to further enhance the ability of all levels of government together to manage and utilize the potentials and resources that exist, whether the potential social-economic communities, natural resources and government assistance. Kudus is one district that pro-investment in Central Java, by having as many as 13.659 UMKM in 2014UU No. 20 of 2004 on UMKM, the empowerment of UMKM itself was an attempt by the government, local government, businesss and society synergilistically. Conceptually UMKM mainly to do with the system itself is empowering UMKM. Empowerment success relies heavily on the participation of UMKM as actors and other stakeholders who as well and was intrumental in this development.